2013
DOI: 10.1152/jn.01085.2012
|View full text |Cite
|
Sign up to set email alerts
|

A role for TREK1 in generating the slow afterhyperpolarization in developing starburst amacrine cells

Abstract: Slow afterhyperpolarizations (sAHPs) play an important role in establishing the firing pattern of neurons that in turn influence network activity. sAHPs are mediated by calcium-activated potassium channels. However, the molecular identity of these channels and the mechanism linking calcium entry to their activation are still unknown. Here we present several lines of evidence suggesting that the sAHPs in developing starburst amacrine cells (SACs) are mediated by two-pore potassium channels. First, we use whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 62 publications
3
19
0
Order By: Relevance
“…To date only one study has confirmed a role for K2P channels in the retina. Ford et al 60,. have shown that TREK-1 contributes to slow after-hyperpolarisation events and regulates the frequency of retinal waves within starburst amacrine cells during early postnatal development.…”
mentioning
confidence: 99%
“…To date only one study has confirmed a role for K2P channels in the retina. Ford et al 60,. have shown that TREK-1 contributes to slow after-hyperpolarisation events and regulates the frequency of retinal waves within starburst amacrine cells during early postnatal development.…”
mentioning
confidence: 99%
“…This same pattern of independent motor activity was also seen in respiratory output from internal intercostal muscles or VII motor roots, suggesting it is a general property of respiratory motor pools. Second, output from lumbar and thoracic roots (which innervate expiratory musculature) has previously been shown to require structures outside of the preBötC and the rostral ventral respiratory group, which are the well-established sources of rhythmic inspiratory drive and premotor innervation to the phrenic motor pool (Miller et al, 1985; Merrill and Lipski, 1987; Sasaki et al, 1991; Iscoe, 1998; Janczewski et al, 2002; de Almeida et al, 2010; Ford and Kirkwood, 2013). These anatomical differences are consistent with independent sources of respiratory drive to different motor pools serving inspiration and expiration, respectively, although we cannot rule out changes in connectivity during maturation (Iscoe, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This hyperpolarization is typically seen after repetitive action potential firing in most central nervous system (CNS) neurons and is mediated by a slowly inactivating K + outward current. Albeit the precise molecular nature of this conductance is yet unclear, there is evidence for involvement of SK‐type Ca 2+ ‐activated K + channels, KCNQ channels, HCN channels, and more recently even TREK1 channels—most probably depending on the cell type (Stocker et al., ; Stackman et al., ; Bildl et al., ; Yue & Yaari, ; Gu et al., ; Fernandez de Sevilla et al., ; Yue & Yaari, ; Gu et al, ; Tzingounis et al, ; Ford et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…AHPs have been classically subdivided by temporal dynamics into fast (fAHP, 2–5 msec), medium (mAHP, 50–100 msec), and slow components (sAHP, 1–2 s; Storm, ). Although it is widely believed that K + outward currents underlie the AHP, the search for the molecular nature of distinct AHP classes (fAHP, mAHP, and sAHP) has revealed a number of K + channels including Ca 2+ ‐activated K + channels, KCNQ channels, hyperpolarization‐activated cyclic nucleotide gate nonselective (HCN) channels, and more recently even tandem pore weak inward rectifier K+ channel‐related K+ channel 1 (TREK1) channels (Stocker et al., ; Stackman et al., ; Bildl et al., ; Yue & Yaari, ; Gu et al., ; Fernandez de Sevilla et al., ; Yue & Yaari, ; Gu et al, ; Tzingounis et al, ; Ford et al., ). In particular, the molecular identity of the sAHP‐mediating K + channel appears to be largely cell‐type specific (see review by Andrade et al., ).…”
mentioning
confidence: 99%